2021
DOI: 10.1017/9781108764971
|View full text |Cite
|
Sign up to set email alerts
|

Race, Rights and Reform

Abstract: Sarah C. Dunstan constructs a narrative of black struggles for rights and citizenship that spans most of the twentieth century, encompassing a wide range of people and movements from France and the United States, the French Caribbean and African colonies. She explores how black scholars and activists grappled with the connections between culture, race and citizenship and access to rights, mapping African American and Francophone black intellectual collaborations from the Paris Peace Conference in 1919 to the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Williams (2005) also found that social criteria are most important for SRI investors in comparison to shareholders' interest and financial criteria. Dunstan (2021) in his blog said that, if an enterprise wants to do value creation, then they must fulfill their responsibility towards respecting human rights. Respecting human rights is one of the important ESG factors and it is the global standard of conduct that should be practiced by all companies and institutional investors.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Williams (2005) also found that social criteria are most important for SRI investors in comparison to shareholders' interest and financial criteria. Dunstan (2021) in his blog said that, if an enterprise wants to do value creation, then they must fulfill their responsibility towards respecting human rights. Respecting human rights is one of the important ESG factors and it is the global standard of conduct that should be practiced by all companies and institutional investors.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…In many ways the Dakar festival colloquium was a continuation of an elite Black and masculinist internationalism that dated back to the beginning of the twentieth century and which included Du Bois's Pan-African Congresses as well as the Présence Africaine conferences coordinated by Alioune Diop and held in Paris and Rome in 1956 and 1959 respectively. 61 Publicly, Alioune Diop's Société Africaine de Culture and UNESCO sponsored the academic colloquium at the festival and this emphasized the elite nature of the organ ization. 62 One writer for Présence Africaine, the Beninese poet Paulin Joachim, later emphasized this connection: "Dakar was the perfect place for this type of meeting.…”
Section: Postwar Racial Landscapesmentioning
confidence: 99%